Changes in adiposity status from childhood to adolescence: a 6-year longitudinal study in Portuguese boys and girls - Leitão, Raquel (2011)
Background: Cross-sectional data show high prevalence of overweight in Portuguese children, but there are few longitudinal studies describing the patterns of obesity development in the young. Aim: To examine the trajectories of obesity from late childhood to adolescence. Subjects and methods: Triceps and subscapular skinfold thickness measurements were carried out in 288 children at age 9 (baseline) and later at age 15 (follow-up). Percentage body fat (%BF) was estimated according to Slaughter equations and the health-related definition of obesity ( ≥ 25%BF in boys and ≥ 30%BF in girls) was used. Results: In boys, the prevalence of obesity decreased from 21.9% to 14.8% (p < 0.05) while in girls it increased from 14.3% to 19.5%. The incidence of obesity in the 6-year study period was 2.6% and 8.3% for boys and girls, respectively (p < 0.05). In comparison with girls, the percentage of boys that reversed obesity was more than 3-fold higher (3% vs 9.7%, p < 0.05). Obesity tracked moderately in both sexes (Kappa = 0.6, p < 0.001). Conclusion: The results indicate a marked sex difference in the incidence and reversal of obesity from late childhood to adolescence that is unfavourable to girls. Consideration of this difference might be important when designing programmes for the prevention and treatment of obesity focusing on this period.